Peran Orang Tua Terhadap Pendidikan Anak Perspektif Pendidikan Islam (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2018)
Parents play an important role in provide education to his son in the family. Parents must pay attention in education particularly education religion to his son according to their parents, although preoccupied with their activities. Parents who he must know the responsibility of very much determines the formation of a couple of families who, and he shall be responsible for what would be its role, then the parents it will lead, educate and grant for the rest of his family in all things. Efforts must be done of parents in education on child by starting teach religious education and guide the implementation of their religious rituals, keep an eye on children and rebuked their behavior when they commit is not a good thing. In terms of material the old man gave his son as any other use send their children and meet immediate needs. Parents must also be able to provide guidance faith, giving exemplary and able to develop growth personality and a sense of responsibility. Consciously parents carrying an obligation to maintain and managing their children to be a useful family.